The Welfare of the Child as a Legal and Extra-Legal Value to be Protected in Civil Proceedings - Bodio, Joanna (Teisė, 2025)
The aim of this article is to show how the ‘welfare of the child’ is implemented in civil proceedings as a legal value (a legal principle) and a non-legal value (a general clause). Therefore, it is necessary to first refer to legal theories defining the concept and relationship between general clauses and legal principles in order to identify procedural and non-procedural provisions and procedural institutions implementing the principle of the welfare of the child in litigation and non-litigious proceedings.The research encompasses Polish Civil Procedural Law and scholarly literature insights regarding the welfare of the child. The analysis has revealed that the introduction of the general clause of ‘the welfare of the child’ into a specific legal provision, as well as the application of the principle of the welfare of the child within various procedural institutions, allows the court, within the limits provided for by law, to make decisions that it considers optimal in the specific situation of the child. Therefore, the Code and non-Code regulations include provisions directly referring to the welfare of the child, but also those in which this concept does not appear, yet there is no doubt that they serve to promote the welfare of the child. This trend in civil proceedings is reflected in the content of general provisions concerning guardianship proceedings, provisions which aim to empower the child and grant them the status of a party in a trial or a participant in non-litigious proceedings, provisions granting the child legal capacity, making the performance of certain acts dependent on the consent of the minor, implementing the right to hear the child, or provisions introducing protection for children appearing as witnesses.
Keywords: child’s welfare; rule of law; general clause; civil proceedings